Multiplexed SSR marker analysis of Diplocarpon coronariae reveals clonality within samples from Middle Europe and genetic distance from Asian and North American isolates - Thomas Oberhänsli; Anna Dalbosco; Virginie Leschenne; Anne Bohr; Sascha Buchleither; Lucius Tamm; Lukas Wille; Srđan G. Aćimović; Fatemeh Khodadadi; Young-Hyun Ryu; Bruno Studer; Hans-Jakob Schärer; et al. (CABI Agriculture and Bioscience)
Abstract Background Apple blotch (AB) caused by Diplocarpon coronariae (Dc) has been established in Europe since 2010. AB is a serious apple disease, mostly in low input orchards and in cider production areas in Northern Italy, Switzerland, Austria and Germany. However, the epidemiology and population genetic structure of this pathogen is unknown. Methods We developed twelve Dc-specific microsatellite markers and screened DNA of both pure fungal isolates and infected apple leaves. The marker data of 313 European samples of Dc were compared to Dc isolates from Asia (n = 7) and the USA (n = 3). Results We found 31 distinct multilocus genotypes (MLGs) in European samples, and seven additional MLGs in the Asian and USA samples. The European samples had the typical genetic signature of a recently introduced species including high clonality, a low number of private alleles and one dominant MLG across all the sampling sites. All European MLGs were genetically distant from those MLGs of Asian and USA origin. Based on the lack of linkage disequilibrium observed, there is evidence that Dc undergoes regular cycles of sexual recombination in the European population, although the sexual stage (apothecia) has not been observed in Europe. Conclusions The twelve newly developed SSR markers reported here provide a useful tool to characterize the population genetic diversity and structure of Dc in Europe. Our study supports the hypothesis that Dc is a recently introduced pathogen in Europe, but of currently unknown origin. Dc has a large effective population size during field epidemics, so we believe that the pathogen has substantial evolutionary potential. Application of the SSR markers to large-scale and diverse Dc samples will help to better understand the epidemiology of AB, which has become a global apple disease, and will help guide effective mitigation strategies based on disease management and resistance breeding.